2022
DOI: 10.1155/2022/6808641
|View full text |Cite
|
Sign up to set email alerts
|

Single Feature Extraction Method of Bearing Fault Signals Based on Slope Entropy

Abstract: As an entropy representing the complexity of sequence, slope entropy (SloE) is applied to feature extraction of bearing signal for the first time. With the advantage of slope entropy in feature extraction, the effectiveness of bearing fault signal diagnosis can be verified. Five different kinds of entropy are selected to be comparative methods for experiments, and they are permutation entropy (PE), dispersion entropy (DE), a version of entropy adapted by PE, which is weighted permutation entropy (WPE), and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Unlike the above entropies, slope entropy (SlopEn) is a new entropy estimator proposed based on symbolic patterns and magnitude information [ 17 ] and has been applied in the underwater acoustic field and medical field many times [ 18 , 19 , 20 , 21 ]. In 2022, SlopEn was introduced into the field of bearing fault diagnosis for the first time, and experimental results showed that, compared with PE and DE, SlopEn could better extract fault information [ 22 ]. However, all the above-mentioned entropy-based bearing fault diagnosis methods suffer from two defects: (i) the methods extract only the fault information of the low-frequency component for the bearing signal, and (ii) there is the problem of threshold selection for SlopEn, and the thresholds usually need to be optimized using an optimization algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the above entropies, slope entropy (SlopEn) is a new entropy estimator proposed based on symbolic patterns and magnitude information [ 17 ] and has been applied in the underwater acoustic field and medical field many times [ 18 , 19 , 20 , 21 ]. In 2022, SlopEn was introduced into the field of bearing fault diagnosis for the first time, and experimental results showed that, compared with PE and DE, SlopEn could better extract fault information [ 22 ]. However, all the above-mentioned entropy-based bearing fault diagnosis methods suffer from two defects: (i) the methods extract only the fault information of the low-frequency component for the bearing signal, and (ii) there is the problem of threshold selection for SlopEn, and the thresholds usually need to be optimized using an optimization algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…It was also a valuable feature in the machine learning ECG signal classification [ 20 ]. The method has been used for other types of signals, such as bearing fault signals [ 21 ] and ship-radiated noise signals [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, SlEn was first proposed by David Cuesta-Frau, and successively applied it to the classification of electroencephalographic (EEG) records and electromyogram (EMG) records [27], classify the activity records of patients with bipolar disorder [28], and the features extraction of fever time series [29]. Then SlEn is also used to extract the features of ship radiated noise signals [30] and bearing fault signals [31].…”
Section: Introductionmentioning
confidence: 99%